ЯЙЛОВЛАРДА ЧОРВА МОЛЛАРИНИ БОҚИШДА ЗООГИГИЕНИК МЕЪЁРЛАР - Ш.Ш.Расулов (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Currently, about 40% of pastures are in crisis. 20-25% yield reduction in pasture areas. The sustainable development of the field is directly related to the productivity and nutritional content of pastures. Restoring the plant cover and increasing the productivity of the crisis pastures is an urgent task today.